Geological polymer as well as preparation method and water storage module thereof - CAO SHUMIN (2018)
The invention discloses a geological polymer as well as a preparation method and a water storage module thereof. The preparation method of the geological polymer comprises the following steps: S1, uniformly mixing an alkali activator, and performing sealed aging; S2, performing a stirring reaction on the alkali activator obtained in the step S1 with coal ash; S3, putting fatty acid into the mixture prepared in the step S2, and performing a stirring reaction so as to obtain geological polymer base slurry; S4, stirring and mixing the geological polymer base slurry obtained in the step 3 with a foaming agent so as to obtain foamed geological polymer base slurry; S5, injecting the foamed geological polymer base slurry obtained in the step S4 into a mold, and performing constant-temperature maintenance, so as to obtain the geological polymer. After sufficient activation of a composite activator, the polymerization degree of the geological polymer prepared from the alkali activator, a composite carboxylic acid acti